2011
DOI: 10.1111/j.1600-051x.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone modelling at fresh extraction sockets: immediate implant placement versus spontaneous healing. An experimental study in the beagle dog

Abstract: The results from this investigation showed that after tooth extraction the buccal socket wall underwent bone resorption at both test and control sites. This resorption appeared to be more pronounced at the implant sites, although the limitations of the histological evaluation method utilized preclude a definite conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
69
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 20 publications
11
69
0
5
Order By: Relevance
“…This phenomenon has been recently described by others (Vignoletti et al. ). Nevertheless, our results are also in agreement with Vignoletti et al.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This phenomenon has been recently described by others (Vignoletti et al. ). Nevertheless, our results are also in agreement with Vignoletti et al.…”
Section: Discussionsupporting
confidence: 75%
“…With respect to the amount of bone modelling taking place in the lingual side of the socket, it is not possible to precisely calculate this parameter in the present material, as implant positioning was performed with respect to the buccal bone, and it is known that the lingual bone is positioned at a more coronal level compared with the buccal bone (Vignoletti et al. )…”
Section: Discussionmentioning
confidence: 99%
“…14,38,39 However, buccal bone alterations may be reduced by the careful selection of implant position and buccal gap distances.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical complications after IIP are especially related to soft tissue alterations in consequence of a coronal shift of the gingival margin, which tend to follow the underlying bone after buccal bone plate remodeling. Importantly, recent studies [15][16][17] showed that alveolar ridge preservation and soft and hard tissue regeneration limit the resorptive process after tooth extraction.…”
Section: Discussionmentioning
confidence: 99%